Pulmonary Open, Robotic, and Thoracoscopic Lobectomy (PORTaL) Study: An Analysis of 5721 Cases. Issue 3 (16th March 2023) - Kent, Michael S.; Hartwig, Matthew G.; Vallières, Eric; Abbas, Abbas E.; Cerfolio, Robert J.; Dylewski, Mark R.; Fabian, Thomas; Herrera, Luis J.; Jett, Kimble G.; Lazzaro, Richard S.; Meyers, Bryan; Mitzman, Brian A.; et al.
Abstract : Objective: The aim of this study was to analyze outcomes of open lobectomy (OL), VATS, and robotic-assisted lobectomy (RL). Summary Background Data: Robotic-assisted lobectomy has seen increasing adoption for treatment of early-stage lung cancer. Comparative data regarding these approaches is largely from single-institution case series or administrative datasets. Methods: Retrospective data was collected from 21 institutions from 2013 to 2019. All consecutive cases performed for clinical stage IA-IIIA lung cancer were included. Neoadjuvant cases were excluded. Propensity-score matching (1:1) was based on age, sex, race, smoking-status, FEV1%, Zubrod score, American Society of Anesthesiologists score, tumor size, and clinical T and N stage. Results: A total of 2391 RL, 2174 VATS, and 1156 OL cases were included. After propensity-score matching there were 885 pairs of RL vs OL, 1, 711 pairs of RL vs VATS, and 952 pairs of VATS vs OL. Operative time for RL was shorter than VATS ( P < 0.0001) and OL ( P = 0.0004). Compared to OL, RL and VATS had less overall postoperative complications, shorter hospital stay (LOS), and lower transfusion rates (all P <0.02). Compared to VATS, RL had lower conversion rate ( P <0.0001), shorter hospital stay ( P <0.0001) and a lower postoperative transfusion rate ( P =0.01). RL and VATS cohorts had comparable postoperative complication rates. In-hospital mortality was comparable between all groups. Conclusions: RL and VATS approaches were associated with favorable perioperative outcomes compared to OL. Robotic-assisted lobectomy was also associated with a reduced length of stay and decreased conversion rate when compared to VATS.